TEACHER’S QUESTIONS USED IN TEACHING ENGLISH AT THE 1ST GRADE STUDENTS OF ONE JUNIOR HIGH SCHOOL IN BANDUNG - Gita Ernita; Tini Apriliani (PROJECT (Professional Journal of English Education), 2020)
Teachers are facilitators that assist students to make the learning process easier and more comfortale. Techer question is a part of learning process. The  aim  of  this  research  is to  find out the types  of  questions  asked  by teachers  in  teaching  and  learning  process.  This  research  is  descriptive  research.  Participant of this research are two English teachers at SMP PGRI Bandung. The  data  collection  used  two  instruments  namely    audio  recording  and  note taking.  From  this  research,  researcher  found  that  open ended questions are mostly occur in the classroom beside ; yes/no questions, short answer   questions,   display   questions,   referential   questions   and   non   retrieval questions. During research, there are three kind of languages used by teachers, they are English, mixed English –Indonesian, and Indonesian.